Pertanggungjawaban Pidana Internasional Mantan Perdana Menteri Bangladesh Sheikh Hasina atas Dugaan Kejahatan terhadap Kemanusiaan - Tasya Fillo Sofia; Wevy Efticha Sary (AHKAM, 2026)
The political crisis and violence in Bangladesh in 2024, which resulted in fatalities and allegations of crimes against humanity, raised legal issues concerning the international criminal responsibility of a head of government. Repressive actions by state authorities, including the use of live ammunition against demonstrators, mass arrests, arbitrary detention, and the shutdown of national internet access, raised questions regarding the international criminal responsibility of Sheikh Hasina as the head of government at the time the events occurred. This study aims to analyze whether the violence in Bangladesh in 2024 fulfilled the elements of crimes against humanity under international criminal law, examine the possibility of Sheikh Hasina’s international criminal responsibility, and assess the validity of the in absentia judgment of the International Crimes Tribunal Bangladesh from the perspective of international law. This study used a normative legal method with statutory, conceptual, and case approaches. Legal materials were obtained through a literature study covering primary, secondary, and tertiary legal materials, and were then analyzed qualitatively based on the principles of international criminal law. The results showed that the use of live ammunition, mass arrests, and the nationwide shutdown of internet access fulfilled the elements of a widespread or systematic attack against a civilian population. Sheikh Hasina’s position as the head of government opened the possibility of criminal responsibility under Article 28 of the Rome Statute. However, the judgment rendered in the absence of the accused and accompanied by the death penalty raises serious concerns regarding the fulfillment of fair trial guarantees as regulated in Article 14 of the ICCPR. The conclusion of this study affirms that the prosecution of serious human rights violations must still be accompanied by full respect for the rights of the accused so that substantive and procedural justice can be achieved in a balanced manner.